An assessment of influential factors developing the intention to use social media sites: A technology acceptance model based approach - Bashir, Tayyeba; Zhongfu, Tan; Sadiq, Burhan; Niaz, Uzma; Anjum, Faiza; Mahmood, Hassan (Frontiers in Psychology, 2022)
The aim of this study is to elaborate the different factors which attract users to use social media sites. These main factors are subjective norms, image, efficiency and satisfaction along with the mediating role of perceived usefulness. Survey method was used to collect data from B2B fashion brands in Pakistan. Convenient sampling technique was used to collect data from targeted respondents. Collected data was analyzed using Smart-PLS 3.3 version. Results express that subjective norms, image, efficiency and satisfaction have positive and significant impact on perceived usefulness and intention to use social media sites in B2B context within Pakistani fashion brands. Results further reveal that perceived usefulness partially mediates the relationship between subjective norms, image, efficiency, satisfaction and intention to use social media sites. This study will enhance the available literature in the area of technology acceptance model (TAM) and will provide useful insights to B2B managers to use efficiently use social media sites for the promotion of their brands. This study is limited to fashion brands, future researchers can expand this model to other area of business.